Neural Correlates of Pair-bonding in a Monogamous Primate - Bales, Karen L. (2007)
The neurobiology of social bonding, despite its relevance to human mental health, has been studied primarily in rodents. In this study we used position emission tomography (PET), registered with structural magnetic resonance imaging (MRI) to investigate central glucose uptake in seventeen males of a monogamous primate species, the titi monkey (Callicebus cupreus). Twelve pair-bonded males (including six with a lesion of the prefrontal cortex) and five lone males were scanned. The five lone males were re-scanned 48 hours after pairing with a female. Significant differences in glucose uptake were found between males in long-term pair-bonds and lone males in areas including the nucleus accumbens, ventral pallidum, medial preoptic area, medial amygdala, and the supraoptic nucleus of the hypothalamus. In paired before and after comparisons, males showed significant changes following pairing in the right nucleus accumbens and ventral pallidum but not in other areas. Lesioned males showed significantly higher uptake in the posterior cingulate cortex than all other males. These results indicate some basic similarities between rodents and primates in the formation and maintenance of selective social bonds, but emphasize the importance of studying long-term maintenance in addition to short-term formation of social bonds.